2021
DOI: 10.1177/07356331211048777
|View full text |Cite
|
Sign up to set email alerts
|

Application of Educational Data Mining Approach for Student Academic Performance Prediction Using Progressive Temporal Data

Abstract: Educators in higher education institutes often use statistical results obtained from their online Learning Management System (LMS) dataset, which has limitations, to evaluate student academic performance. This study differs from the current body of literature by including an additional dataset that advances the knowledge about factors affecting student academic performance. The key aims of this study are fourfold. First, is to fill the educational literature gap by applying machine learning techniques in educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…Access to internet, Age, Economic dependence, Employment status, Ethnicity, Family Highest Education Level, Family income, Family size, Gender, Health status, House to university distance, Lives in town or village, Marital Status, Nationality, Parents job, Parents occupation, Parents qualification, Parent status, Total income [17], [22], [23], [26], [28]- [31], [35], [38], [41]- [43], [46], [48]- [55], [57]- [60], [63]- [65], [67], [68], [70]- [77] Leonardo…”
Section: Factor Variables Authors Who Consider Variables Of This Factormentioning
confidence: 99%
See 3 more Smart Citations
“…Access to internet, Age, Economic dependence, Employment status, Ethnicity, Family Highest Education Level, Family income, Family size, Gender, Health status, House to university distance, Lives in town or village, Marital Status, Nationality, Parents job, Parents occupation, Parents qualification, Parent status, Total income [17], [22], [23], [26], [28]- [31], [35], [38], [41]- [43], [46], [48]- [55], [57]- [60], [63]- [65], [67], [68], [70]- [77] Leonardo…”
Section: Factor Variables Authors Who Consider Variables Of This Factormentioning
confidence: 99%
“…Table 3 shows the variables found that belong to the factor and the authors who used some of these for the development of their models. [28], [35], [45], [47], [49], [50], [55], [57], [59], [65], [70], [72]- [79] Source: Own work.…”
Section: E-learning Factormentioning
confidence: 99%
See 2 more Smart Citations
“…First, data analysis and psychological findings provide meaningful information and correlation between factors such as frustration, the COVID-19 pandemic, E-learning, and the performance evaluation of at-risk students [7][8][9]. Second, the prior students' performance prediction approaches used the psychological findings and data analysis contributions to optimize performance computation models [10][11][12][13][14]. ese various groups of studies are still limited in obtaining an optimized students' performance prediction system based on insightful frustration severity modeling [15][16][17][18][19].…”
Section: Introduction E Outbreak Of Covid-19 and E-learning With Massivementioning
confidence: 99%